Investment Banking : Valuation, LBOs, M & a, and IPOs (Book + Valuation Models). - Pearl, Joshua (John Wiley & Sons, Incorporated, 2022)
An essential, all-in-one guide to investment banking and valuation, complete with downloadable models - this new edition reflects valuable contributions from Nasdaq and the global law firm Latham & Watkins LLP plus access to the online valuation models and course. The thoroughly revised Third Edition of Investment Banking: Valuation, LBOs, M & A, and IPOs (Book + Valuation Models) delivers the most current discussion of valuation and deal-making fundamentals essential to the work of investment bankers, private equity professionals, hedge fund investors, corporate lawyers, executives, and students. Drawing on over four decades of combined experience in investment banking and investing, authors Joshua Rosenbaum and Joshua Pearl explain how to perform the valuation work and financial analysis at the core of Wall Street - comparable companies, precedent transactions, DCF, LBO, M & A analysis ... and now IPO analytics and valuation. Using a step-by-step, how-to approach for each methodology, the authors build a chronological knowledge base and define key terms, financial concepts, and processes throughout the book. Now, over 10 years after the release of the first edition, the book is more relevant and topical than ever. The book has sold over 250,000 copies and is used in over 200 universities globally. It has become a go-to resource for investment banks, private equity, investment firms, and corporations undertaking M & A transactions, LBOs, IPOs, restructurings, and investment decisions. While the fundamentals haven't changed, the environment must adapt to changing market developments and conditions. As a result, Rosenbaum and Pearl have updated their widely-adopted book accordingly, turning the latest edition into a unique and comprehensive training package. The Third Edition includes six downloadable valuation model templates: Comparable Companies Analysis, Precedent Transactions Analysis, Discounted Cash Flow Analysis, Leveraged Buyout Analysis, M & A Analysis, and IPO Valuation, available at www.wiley.com/go/investmentbanking3e.